Population genomics of selectively neutral genetic structure and herbicide resistance in UK populations of Alopecurus myosuroides. Issue 3 (11th December 2020) - Dixon, Andrea; Comont, David; Slavov, Gancho T; Neve, Paul
Abstract: BACKGROUND: Alopecurus myosuroides (blackgrass) is a major weed in Europe with known resistance to multiple herbicide modes of action. In the UK, there is evidence that blackgrass has undergone a range expansion. In this paper, genotyping‐by‐sequencing and population‐level herbicide resistance phenotypes are used to explore spatial patterns of selectively neutral genetic variation and resistance. We also perform a preliminary genome‐wide association study (GWAS) and genomic prediction analysis to evaluate the potential of these approaches for investigating nontarget site herbicide resistance. RESULTS: Blackgrass was collected from 47 fields across the British Isles and up to eight plants per field population ( n = 369) were genotyped by Restriction site‐associated DNA (RAD)‐sequencing. A total of 20 426 polymorphic loci were identified and used for population genetic analyses. Phenotypic assays revealed significant variation in herbicide resistance between populations. Population structure was weak ( F ST = 0.024–0.048), but spatial patterns were consistent with an ongoing westward and northward range expansion. We detected strong and consistent Wahlund effects ( F IS = 0.30). There were no spatial patterns of herbicide resistance or evidence for confounding with population structure. Using a combination of population‐level GWAS and genomic prediction we found that the top 20, 200, and 2000 GWAS loci had higher predictive abilities for fenoxaprop resistance compared to all markers. CONCLUSION: There is likely extensive human‐mediated gene flow between field populations of the weed blackgrass at a national scale. The lack of confounding of adaptive and neutral genetic variation can enable future, more extensive GWAS analyses to identify the genetic architecture of evolved herbicide resistance. © 2020 Society of Chemical Industry Abstract : There was little population structure amongst UK blackgrass, but evidence of a recent range expansion. Lack of confounding of neutral and adaptive genetic variation is favourable for future genome‐wide association study approaches.